2017
DOI: 10.3389/fpls.2017.01757
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Plasma Membrane H+-ATPase in Plant Responses to Aluminum Toxicity

Abstract: Aluminum (Al) toxicity is a key factor limiting plant growth and crop production on acid soils. Increasing the plant Al-detoxification capacity and/or breeding Al-resistant cultivars are a cost-effective strategy to support crop growth on acidic soils. The plasma membrane H+-ATPase plays a central role in all plant physiological processes. Changes in the activity of the plasma membrane H+-ATPase through regulating the expression and phosphorylation of this enzyme are also involved in many plant responses to Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 100 publications
1
55
0
1
Order By: Relevance
“…These results further support the hypothesis that PM H 1 -ATPase activity contributes to the defective V-ATPase-induced root Al resistance. The PM H 1 -ATPase mediates H 1 efflux into the apoplast (Gaxiola et al, 2007;Zhang et al, 2017). To examine whether PM-ATPase activity affects apoplastic pH in wild-type and vha-a2 vha-a3 mutant roots during Al exposure, we measured the pH value in the nonbuffer solutions containing 250 mM Al 31 on which the wild type or the vha-a2 vha-a3 mutant was grown, and we found that the vha-a2 vha-a3 mutant caused a more significant pH decrease than the wild type after 3 h of incubation (Supplemental Fig.…”
Section: V-atpase and V-ppase Activity Are Repressed Upon Al Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…These results further support the hypothesis that PM H 1 -ATPase activity contributes to the defective V-ATPase-induced root Al resistance. The PM H 1 -ATPase mediates H 1 efflux into the apoplast (Gaxiola et al, 2007;Zhang et al, 2017). To examine whether PM-ATPase activity affects apoplastic pH in wild-type and vha-a2 vha-a3 mutant roots during Al exposure, we measured the pH value in the nonbuffer solutions containing 250 mM Al 31 on which the wild type or the vha-a2 vha-a3 mutant was grown, and we found that the vha-a2 vha-a3 mutant caused a more significant pH decrease than the wild type after 3 h of incubation (Supplemental Fig.…”
Section: V-atpase and V-ppase Activity Are Repressed Upon Al Stressmentioning
confidence: 99%
“…The AHA genes are differentially expressed in Arabidopsis tissues, and eight of them (AHA1-AHA4, AHA7, AHA8, AHA10, and AHA11) are expressed in roots (Ueno et al, 2005). Despite the fact that apoplastic acidification is generally observed upon Al stress (Zhang et al, 2017), little is known about how PM H 1 -ATPase is linked to Al response in Arabidopsis. The PM H 1 -ATPase activity has been hypothesized to be related to the activity of vacuolar H 1 pump (Li et al, 2005;Cho et al, 2012), which is constituted by V-ATPase and V-PPase (Gaxiola et al, 2007).…”
mentioning
confidence: 99%
“…Interestingly, our results showed that both H 2 S and NO are required for Al‐stimulated GmMATE expression (Figure a). In addition to citrate transporter, PM H + ‐ATPase was also reported to be responsible for Al‐induced citrate secretion in plants (Zhang et al, ). PM H + ‐ATPase can exclude H + outside the cell membrane to create an electrochemical gradient, thus providing a driving force for the activation of secondary transporters.…”
Section: Discussionmentioning
confidence: 99%
“…This can result in changes in cytoplasmic Ca 2+ homeostasis, which controls cell signaling, metabolism and cell-growth processes including root development 110 . Al 3+ stress induces changes in the expression and activity of the plasma membrane H + -ATPase that controls cytosolic pH and membrane potentials 111 .…”
Section: Discussionmentioning
confidence: 99%